Le raisonnement clinique de l’infirmier en service d’urgence : ajustements, communication et transmission des informations pour optimiser les soins au malade - Maurine Malterre Alexandra (Questions Vives)
“So, tell me what’s happening to you?” The typical introduction of an examination carried out by a registered nurse (IDE, in French) when welcoming a patient in ED to perform a “situational diagnosis”. Gathered data analysis during the self-confrontation interviews with registered nurses, uses the conceptual framework of professional didactics. The healthcare providers’ speeches make about their interview guide, demonstrate continuous adjustments according to the answers given by the patient, but also depending on indicators perceived and selected from the patient while expressing and communicating or not, by the way. But what we initially mentioned as an adaptation phenomenon, gradually took us on the path of adjustment within the historical and cultural meaning of Vygotsky. Our research lingered over the language dimension of IDE. What logic(s), what reasoning(s) do they follow in these adjustments? To improve the initial training of nurses, we question the pedagogical methods which would support the idea of a relevant decoding of the patient’s speech into understandable elements by medical and paramedical board and a synthetic and efficient information transmission.